LOCAL GOVERNMENT ADMINSTRATIONSYSTEMS AS A PANACEA FOR RURAL DEVELOPMENT AND TRANSFORMATION IN BUNGOKHO SUB-COUNTY IN MBALE DISTRICT - MUBIYI I_BPAM_2024.pdf (My University, 2024)
Despite of various policies and programs implemented to transform rural areas, many rural areas are still underdeveloped characterized by poverty and marginalization. This study assessed how local governments are a panacea to rural development and transformation. Specifically, the study investigated the how promoting community participation has enhanced rural development and assess how improving service delivery has promoted rural development and transformation in Bungokho Sub County in Mbale district. It also establishes how planning and passing bylaws has promoted rural development in Bungokho Sub County in Mbale district. The study used cross-sectional design to analyze data from the study area with the help of both qualitative and quantitative methods. Probability and non-probability sampling techniques were used to select study subjects and data was collected from 80 participants in the study area. Questionnaires together with interview guide were used to collect data from study subjects and the researcher data control tools validity and reliability) were used to determine the capability of research tools yield valid and reliable data. Statistical data was presented using tables (quantitative analysis) while data from interviews was presented in form of explanations and illustrations (qualitative analysis). The study found that supporting community participation by local governments helps to build and sustains cohesive communities and community participation leads to improved outcomes. Also supporting community participation by local governments helps to promotes access to resources and community empowerment and community participation help to promote sustainable decision making. Supporting community participation drives social transformation of rural areas and this was mentioned by participants in the findings. Other findings of the study show that undertaking a consultative decision making process on service delivery through has improved service provision to rural areas and there is equal participation of communities in policy and implementation for service provision as revealed by the study findings. Also supporting community participation by local governments is vital for improving access to rural services by communities and engaging communities in the provision of services to promote community ownership and this was mentioned by the participants in the study findings. Additionally, there is no discrimination against persons on basis of their gender or social standing and this has promoted gender equality in policy and decision making and there is separation of powers among different arms of government and this has encouraged local autonomy. Also semi-autonomous laws are promulgated by local governments to help promote rural development and there is no conflict of interest among staffs during planning for rural areas. The researcher recommended increasing funding to local government will help enhance their effectiveness and efficiency as well as building capacity of local governments to implement and monitor various projects and program geared towards rural transformation